2017
DOI: 10.3390/ma10080904
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance Evaluation of Self-Compacting Concrete with Fine and Coarse Recycled Aggregates from the Precast Industry

Abstract: This paper intends to evaluate the feasibility of reintroducing recycled concrete aggregates in the precast industry. The mechanical properties of self-compacting concrete (SCC) with incorporation of recycled aggregates (RA) (coarse recycled aggregates (CRA) and fine recycled aggregates (FRA)) from crushed precast elements were evaluated. The goal was to evaluate the ability of producing SCC with a minimum pre-established performance in terms of mechanical strength, incorporating variable ratios of RA (FRA/CRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 15 publications
1
34
0
3
Order By: Relevance
“…On the other hand, Corinaldesi and Moriconi [18] studied the joint use of CRA and FRA in the production of SCC, concluding that while the use of fine recycled aggregates (FRA, used to replace sand) negatively affected compressive strength, the latter remained unchanged when CRA was used as a replacement of coarse natural aggregates (CNA). In the same sense, Santos et al [19], who conducted a study on the mechanical performance evaluation of SCC with FRA and CRA from the precast industry, concluded that the RA used performed better than reported in similar works. They also concluded that 25% RA, 50% RA, and 100% CRA mixes exhibited satisfactory mechanical and durability behavior for the production of concrete with structural functions.…”
Section: Introductionmentioning
confidence: 79%
“…On the other hand, Corinaldesi and Moriconi [18] studied the joint use of CRA and FRA in the production of SCC, concluding that while the use of fine recycled aggregates (FRA, used to replace sand) negatively affected compressive strength, the latter remained unchanged when CRA was used as a replacement of coarse natural aggregates (CNA). In the same sense, Santos et al [19], who conducted a study on the mechanical performance evaluation of SCC with FRA and CRA from the precast industry, concluded that the RA used performed better than reported in similar works. They also concluded that 25% RA, 50% RA, and 100% CRA mixes exhibited satisfactory mechanical and durability behavior for the production of concrete with structural functions.…”
Section: Introductionmentioning
confidence: 79%
“…Obtaining cement-based materials made with RA (obtained from the treatment of C&DWs) has been one of the most studied applications. Although, indeed, there are currently some reliable studies that support the use of C&DW in conventional concrete [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], in recent years some studies on the use of RA have begun to be published with self-compacting concrete (SCC), although they are still rare [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Most of these studies compare the various fresh and hardened properties of SCC with RA and without RA (natural aggregates), apart from SCC mix design.…”
Section: Introductionmentioning
confidence: 99%
“…The use of recycled sand is not allowed by the Spanish Instruction for Structural Concrete [31] even though some studies show that substitutions of up to 10% do not produce any significant variations in the characteristics of concrete [15,17,19]. Currently, Instruction EHE-08 allows the partial addition (<20% weight) of coarse recycled concrete aggregates as replacement of natural aggregates.…”
Section: Introductionmentioning
confidence: 99%